The development of a condition survey protocol (csp) 1 matrix for visual building inspection - Che-Ani, A.I.; Ali, A.S.; Tahir, M.M.; Abdullah, N.A.G.; Tawil, N.M. (2010)
Building inspection is one of the key components of building maintenance. The primary purpose of performing a building inspection is to evaluate the building’s condition. Without inspection, it is difficult to determine a built asset’s current condition, so failure to inspect can contribute to the asset’s future failure. Traditionally, a longhand survey description has been widely used for property condition reports. Surveys that employ ratings instead of descriptions are gaining wide acceptance in the industry because they cater to the need for numerical analysis output. These kinds of surveys are also in keeping with the new RICS HomeBuyer Report 2009. In this paper, we propose a new assessment method, derived from the current rating systems, for assessing the building’s condition and rating the seriousness of each defect identified. These two assessment criteria are then multiplied to find the building’s score, which we called the Condition Survey Protocol (CSP) 1 Matrix. Instead of a longhand description of a building’s defects, this matrix requires concise explanations about the defects identified, thus saving on-site time during a building inspection. The full score is used to give the building an overall rating: Good, Fair or Dilapidated. Our overall findings reflect the reliability of the CSP1 Matrix.